Strategi Pasukan Amal Sholeh Melalui Gerakan Infak Beras Dalam Meningkatkan Kesejahteraan Pondok Pesantren Dan Yayasan Kota Palangka Raya - Dien, Yoshidayah; Lisnawati, Lisnawati; Syarifuddin, Syarifuddin (Jurnal Iqtisaduna, 2024)
The aim of this research is to analyze and describe the strategies carried out by the Sholeh Charity Forces (PASKAS) in Islamic boarding schools and foundations. The method used in this research is qualitative with a descriptive approach. Research data sources are secondary and primary data collected through observation and interviews as well as books, scientific journals, articles, the internet and other library sources. Data collection techniques use observation, interviews and documentation. By using three key informants, namely the Chairman, Deputy and Treasurer of the Sholeh Charity Force (PASKAS). This research data analysis technique uses four stages, namely data collection, data reduction, data presentation and drawing conclusions. The research results show that the Sholeh Charity Force (Paskas) strategy includes direct communication, distributing piggy banks, social media messages, and visits to foster parents' homes. The supporting factors include the Sholeh Charity Team, foster parents, and transportation, while the inhibiting factors are that rice can only be distributed after donations have been collected and transportation is still limited.